Nouvelles puissances financières et centres de pouvoir - Bertin, Gilles (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
Financial power alone is not sufficient if a state is to exercise an important influence. The former must be coterminous with other forms of power : military, ideological or religious, etc. ... in order for the country to claim a position of limited leadership. Financial power therefore would appear to be only one of the components of total power as a means and not as a final result.Should a limited financial power appear not capable of changing the equilibrium of international markets and, via that, the equilibrium of political relations, it nevertheless is of such a nature, by the disturbances that it can provoke in their operation, to create instability in the latter and in relations among states.The conjuncture of these different points demonstrates clearly that if the rise of the new financial petro-powers can, only lead to gradual change in the relations in this field, it remains sufficiently dangerous to provoke unexpected economic and political disturbances.